Biological control of an invasive pest eases pressures on global commodity markets - Wyckhuys, Kris A.G.; Zhang, Wei; Prager, Steven D.; Kramer, D.B.; Delaquis, Erik; Gonzalez Rodriguez, Carlos Eduardo; Werf, W. van der (IOP Publishing, 2018)
In an increasingly globalized world, invasive species cause major human, financial, and environmental costs. A cosmopolitan pest of great concern is the cassava mealybug Phenacoccus manihoti (Hemiptera: Pseudococcidae), which invaded Asia in 2008. Following its arrival, P. manihoti inflicted measurable yield losses and a 27% drop in aggregate cassava production in Thailand. As Thailand is a vital exporter of cassava-derived commodities to China and supplies 36% of the world's internationally-traded starch, yield shocks triggered price surges and structural changes in global starch trade. In 2009 a biological control agent was introduced in Asia-the host-specific parasitoid, Anagyrus lopezi (Hymenoptera: Encyrtidae). This parasitoid had previously controlled the cassava mealybug in Africa, and its introduction in Asia restored yield levels at a continent-wide scale. Trade network and price time-series analyses reveal how both mealybug-induced production loss and subsequent parasitoid-mediated yield recovery coincided with price fluctuations in futures and spot markets, with important cascading effects on globe-spanning trade networks of (cassava) starch and commodity substitutes. While our analyses may not imply causality, especially given the concurrent 2007–2011 food crises, our results do illuminate the important interconnections among subcomponents of the global commodity system. Our work underlines how ecologically-based tactics support resilience and safeguard primary productivity in (tropical) agro-ecosystems, which in turn help stabilize commodity markets in a similar way as pesticide-centered approaches. Yet, more importantly, (judiciously-implemented) biological control can deliver ample 'hidden' environmental and human-health benefits that are not captured by the prices of globally-traded commodities.